URETHRAL INJURY AS A RARE COMPLICATION OF CIRCUMCISION: A CASE REPORT AND LITERATURE REVIEW - Suwarno, Budi; Gumilar, Ogi Bahaurini; Rozidi, Achmad Romy Syahrial; Zharfan, Rahmat Sayyid (Indonesian Journal of Urology, 2022)
Objective: In this report, we describe the case of urethral injuries after circumcision. Case(s) Presentation: A 5-year-old male came to the urology clinic complaining of urine seeping through the gauze-covered wound. The patient had undergone circumcision. Before the procedure, the patient could generally urinate through the external urethral orifice. His parent realized that the urine was flowing out through the circumcision scar instead of the external orifice. Even though the wound was open and wet, he felt painless when urinating. After cleaning the wound, it appeared that there was a sizeable chromic catgut thread knotted on the right corpus cavernosum. The pendular urethra was cut widely; therefore, the urine came out of this spot. A six French Foley catheter was inserted over the external urethral orifice, the cut urethra towards the bladder. The injured urethra was expected to be attached to simplify the next six-month operation by inserting this urinary catheter. Discussion: Urethral injury post circumcision is rarely reported, but this complication is dangerous due to its morbidity and long-term impact. The paradigm shift from two-stage repair to one-stage repair has developed. Mathieu’s modified technique and the Snodgrass technique are recommended. Conclusion: Urethral injury during circumcision can be devastating. The repair technique for urethral trauma depends on the involvement and condition of the surrounding soft tissue, also the size of the tissue damage.